DIAGNOSIS TUBERKULOSIS PARU MENURUT KEKERAPAN PEMERIKSAAN DAHAK - Larissa Larissa; Ida Parwati; A K Sugianli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Nowadays in Indonesia, three times (first spot-second in the morning-third spot) microscope sputum examination to find acid fastbacilli is used to diagnose pulmonary tuberculosis (TB). WHO policy (2007) recommends a reduction of sputum smears from three upto two times. The International Standards for Tuberculosis (2009) stated that the suspected pulmonary TB patients should have at leasttwo sputum specimens for microscopic examination with one early morning sputum. The aim of this study is to know whether pulmonaryTB can be confirmed only by two sputum specimen in the investigation. The subjects consist of patients who were examined three timesof their sputum at the Microbiology Laboratory of Clinical Pathology Department, at Hasan Sadikin Hospital from 2011–2012 (2 yearsperiod). This study used analytical retrospective method, with investigation agreement between the two first sputum (one of the specimenwas the morning sputum) with the third sputum using kappa coefficient and McNemar test. During the study between 2011–2012, therewere examined 3744 TB suspected patients. There is an excellent agreement (k=0.835) between the two times examination of the firstsputum and the third one. The positive possibility of the third sputum when the first two specimens were negative is only 1.7% (p=0.000).Based on this study there is an excellent agreement between the two times sputum examination with the third one. That means twosputum specimen can be used for the confirmation of pulmonary TB.